Weaknesses of Administrative Sanctions for Construction Services: Analysis of AUPB and its Impact on Effectiveness - Nurliana Ritonga; Triono Eddy; Onny Medaline (Universitas Islam Sultan Agung, 2026)
The provision of construction services plays a strategic role in national development, but in practice it is still marred by various violations that indicate weak compliance with regulations, technical standards, and work contracts. This study aims to analyze the nature of violations in construction services, examine the application of the General Principles of Good Governance (AUPB) in imposing administrative sanctions, and evaluate the effectiveness of administrative sanction regulations in ensuring legal compliance. The research method used is normative legal research with a statutory and conceptual approach, supported by an analysis of relevant primary and secondary legal materials. The results show that violations in construction services are systemic and multidimensional, and have the potential to develop from administrative violations to civil and criminal offenses. The application of AUPB in imposing administrative sanctions has not been optimal, as reflected in inconsistencies, lack of transparency, and weak accountability. Furthermore, the regulation of administrative sanctions is still general and does not provide clear parameters regarding the classification of violations and the proportionality of sanctions, thus implicating its low effectiveness as a law enforcement instrument. In conclusion, the effectiveness of administrative sanctions in construction services has not been fully able to encourage compliance and ensure orderly construction implementation. Therefore, it is necessary to update more operational regulations, strengthen the supervisory system, and internalize the AUPB in government practices in order to realize law enforcement that is fair, accountable, and oriented towards protecting public interests.